The Illegal Wildlife Trade in Poland – Crime Control Models - Edyta Drzazga (Przegląd Prawniczy Uniwersytetu im. Adama Mickiewicza, 2022)
Wildlife traffickindg of endangered species is an international crime that is increasing in in terms of its significance and position in the global crime hierarchy. This phenomenon is a significant subject of research for both traditional and green criminology. The representatives of green criminology, when discussing the criminal policy in matters related to green crimes, refer to its broad meaning. From this perspective, “green criminal policy” includes: a) the legal and social approach, b) a regulatory system that emphasizes social arrangements, norms and reforms in the production and consumption system; and c) a system of social interactions. Each of these models is presented in the article. In this context, the results of qualitative research on the state of the social control of illegal trade in wild fauna and flora in Poland will also be cited.